Fish muscle: The exceptional case of notothenioids - Fernandez, Daniel Alfredo; Calvo, Jorge (Fish Physiology and Biochemistry)
Fish skeletal muscle is an excellent model for studying muscle structure and function, since it has a very well-structured arrangement with different fiber types segregated in the axial and pectoral fin muscles. The morphological and physiological characteristics of the different muscle fiber types have been studied in several teleost species. In fish muscle, fiber number and size varies with the species considered, limiting fish maximum final length due to constraints in metabolites and oxygen diffusion. In this work, we analyze some special characteristics of the skeletal muscle of the suborder Notothenioidei. They experienced an impressive radiation inside Antarctic waters, a stable and cold environment that could account for some of their special characteristics. The number of muscle fibers is very low, 12,700-164,000, in comparison to 550,000-1,200,000 in Salmo salar of similar sizes. The size of the fibers is very large, reaching 600 μm in diameter, while for example Salmo salar of similar sizes have fibers of 220 μm maximum diameter. Evolutionary adjustment in cell cycle length for working at low temperature has been shown in Harpagifer antarcticus (111 h at 0°C), when compared to the closely related sub-Antarctic species Harpagifer bispinis (150 h at 5°C). Maximum muscle fiber number decreases towards the more derived notothenioids, a trend that is more related to phylogeny than to geographical distribution (and hence water temperature), with values as low as 3,600 in Harpagifer bispinis. Mitochondria volume density in slow muscles of notothenioids is very high (reaching 0.56) and since maximal rates of substrate oxidation by mitochondria is not enhanced, at least in demersal notothenioids, volume density is the only means of overcoming thermal constraints on oxidative capacity. In brief, some characteristics of the muscles of notothenioids have an apparent phylogenetic component while others seem to be adaptations to low temperature. Fil: Fernandez, Daniel Alfredo. Consejo Nacional de Investigaciones ...